Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1159/000488304
|View full text |Cite
|
Sign up to set email alerts
|

The Vasopressin System in the Risk of Diabetes and Cardiorenal Disease, and Hydration as a Potential Lifestyle Intervention

Abstract: Background: Type 2 diabetes, chronic kidney disease (CKD) and its cardiovascular complications are increasing as health problems worldwide. These diseases are interrelated with overlapping occurrence and once diabetes is established, the risk of cardiorenal disease is dramatically elevated. Thus, a search for unifying modifiable risk factors is key for effective prevention. Summary: Elevated fasting plasma concentration of vasopressin, measured with the marker copeptin, predicts new onset type 2 diabetes as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 67 publications
(70 reference statements)
0
41
0
Order By: Relevance
“…Recent short-term clinical trials have shown that increased water intake can reduce concentrations of plasma copeptin, fasting blood glucose and glucagon in healthy participants. 13,49 Another study also found that increased water consumption resulted in decreased copeptin concentrations in participants with chronic kidney disease, however, no differences in rates of eGFR decline were observed in participants with or without increased water intake. 50 Mechanisms leading to increased AVP, and thus copeptin, in diabetes are also incompletely elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Recent short-term clinical trials have shown that increased water intake can reduce concentrations of plasma copeptin, fasting blood glucose and glucagon in healthy participants. 13,49 Another study also found that increased water consumption resulted in decreased copeptin concentrations in participants with chronic kidney disease, however, no differences in rates of eGFR decline were observed in participants with or without increased water intake. 50 Mechanisms leading to increased AVP, and thus copeptin, in diabetes are also incompletely elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…The net effect of increased Na + transport is increased renal O 2 consumption, as the majority of oxygen consumed by the kidney is used to support the active reabsorption of Na + . Circulating AVP can also stimulate systemic/renal vasoconstriction, platelet aggregation and hepatic glucose production (V1a receptor) and cortisol secretion (V1b receptor), resulting in hypertension, microalbuminuria, hyperglycemia and insulin resistance, typical features attributed to the development and progression of CVD and worse kidney function . As such, AVP is a potential modifiable risk factor and novel target for future diabetes treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations